GE_GERICHTE C/2153/2015 vom 8. Juli 2015 - GE Cour de justice (2015)
CONCURRENCE DÉLOYALE; MESURE PROVISIONNELLE; COMPÉTENCE RATIONE LOCI; DÉNIGREMENT | CL.5.3; CL.31; LDIP.10; LDIP.132; CPC.261; CPC.263; LCD.3.a